2003
DOI: 10.1177/1362361303007002002
|View full text |Cite
|
Sign up to set email alerts
|

Parental Identification of Early Behavioural Abnormalities in Children with Autistic Disorder

Abstract: The aim of the study was to identify early behavioural abnormalities in children later diagnosed with autistic disorder. Accurate identification of such deficits has implications for early diagnosis, intervention and prognosis. The parents of 153 children with autistic disorder completed a questionnaire asking them to describe early childhood behaviours of concern and to recall the age of onset. Core deficit-linked behaviours were then identified and the ontogeny of their development was noted. Behaviour categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
3
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 61 publications
7
97
3
12
Order By: Relevance
“…São crianças que não voltam a atenção quando seu nome é chamado, que não buscam compartilhar interesses. Young et al 31 apontam algumas manifestações precoces que poderiam ser observadas pelos pais em idades em média inferiores aos 2 anos, como falta de interesse por brinquedos, desinteresse em compartilhar objetos e experiências de que goste, pobre contato visual, intolerância a contato físico, posturas e medos inusuais, problemas alimentares, necessidade de rotinas e rituais, problemas alimentares, movimentos e comportamentos estereotipados, pouca atenção a adultos, crises de birra, regressão ou atraso na linguagem, comportamentos obsessivos, falta de brincadeiras imitativas, interesses restritos e estereotipados e deficiência também na linguagem não-verbal, como apontar. A fixação e seguimento oculares dirigidos a rostos humanos estão comprometidos, e esta é uma manifestação precoce 32 .…”
Section: Transtornos Invasivos Do Desenvolvimento (Condições Pertenceunclassified
“…São crianças que não voltam a atenção quando seu nome é chamado, que não buscam compartilhar interesses. Young et al 31 apontam algumas manifestações precoces que poderiam ser observadas pelos pais em idades em média inferiores aos 2 anos, como falta de interesse por brinquedos, desinteresse em compartilhar objetos e experiências de que goste, pobre contato visual, intolerância a contato físico, posturas e medos inusuais, problemas alimentares, necessidade de rotinas e rituais, problemas alimentares, movimentos e comportamentos estereotipados, pouca atenção a adultos, crises de birra, regressão ou atraso na linguagem, comportamentos obsessivos, falta de brincadeiras imitativas, interesses restritos e estereotipados e deficiência também na linguagem não-verbal, como apontar. A fixação e seguimento oculares dirigidos a rostos humanos estão comprometidos, e esta é uma manifestação precoce 32 .…”
Section: Transtornos Invasivos Do Desenvolvimento (Condições Pertenceunclassified
“…Interestingly, the autistic children without regression were significantly older when they showed their most mature level of motor control whilst lying prone or supine, whereas the autistic group with regression only differed in their growth curve in the later-developing milestone of walking, leading the authors to suggest "an active pathological process" disrupting motor domains (p. 12). Other reports of the earliest emerging autistic symptoms, although they do not specify whether they discuss autism with or without regression, do indeed note motor dysfunction within the first 12 months (Guinchat et al, 2012;Young, Brewer, & Pattison, 2003). 6 Aside from milestones, abnormalities in lying (Esposito, Venuti, Maestro, & Muratori, 2009) have been reported in autistic infants, as have unusual posturing (Baranek, 1999) and differences or reductions in general spontaneous movement (Phagava et al, 2008;Zappella et al, 2015).…”
mentioning
confidence: 99%
“…These children do not respond when called by their names, and do not seek to share interests. Young et al 31 reveal some early symptoms that may be observed by parents at ages on average lower than two years, such as lack of interest in toys, no interest in sharing cherished objects or experiences, poor eye contact, intolerance of physical contact, unusual postures and fears, eating disorders, necessity for routines and rituals, stereotyped movements and behaviors, little attention to adults, temper tantrums, language regression or delay, obsessive behaviors, lack of pretend play, restricted and stereotyped interests, deficiency in nonverbal language (e.g. : lack of pointing).…”
Section: Introductionmentioning
confidence: 99%